The Deviation Degree of Investment Level of Sports Industry in China—A Case Study of Listed Sports Companies - Jin Wang, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The purpose of this paper is to study the degree of deviation from the level of investment in China's sports industry. Subjects of this paper are 39 companies engaged in the sports industry of China and listed in Shanghai or Shenzhen stock market, and a two-tier Stochastic Frontier Approach (SFA) model was built to study their panel data from 2007 to 2021 and figure out the influence of financing constraints and agency costs on the deviation of investment level of these subjects. The results suggest that: Both financing constraints and agency costs have a significant impact on the investment level of subjects, and the influence degree of financing constraints is slightly higher; on average, under the combined effect of financing constraints and agency costs, the investment level of subjects is 1.72% lower than the optimal investment level; the influence of financing constraints and agency costs on the deviation of investment level of subjects varies with the year, overall speaking, the influence of financing constraints is larger; for subjects of different property ownership types, there are differences in the degree of deviation of their investment level from the optimal investment level; compared with non-state-owned companies, the state-owned companies are more likely to have insufficient investment. The policy and practical recommendation of this paper is: Government should reduce financing constraints by means of optimizing relevant legal provisions and regulating the tax rates.